Neurological Complication of Chikungunya Fever: Guillain Barre Syndrome - A Case Report (Bangladesh Medical Journal, 2019)
Chikungunya fever has been known   as reemerging disease since 2005. Its feature is more or less like dengue fever. Major outbreak occurred in Bangladesh in 2017. Lot of complications can occur in patient suffered from it. We report a Chikungunya case presenting with Guillain-Barré syndrome (GBS) with sensory involvement and bowel- bladder dysfunction who responded to plasma pharesis. Laboratory parameters and temporality support that GBS in the complication of Chikungunya.Bangladesh Med J. 2017 Sep; 46 (3): 97-99